STATUS PERKAWINAN TERHADAP PASANGAN SUAMI ATAU ISTRI YANG BERPINDAH AGAMA MENURUT KOMPILASI HUKUM ISLAM - NIM. A1011171076, FINA NAFISA KAMILA (Fakultas Hukum Universitas Tanjungpura, 2022)
AbstractA marriage has strong power and legality if it is legally recognized. A marriage can be broken if one of the conditions of marriage cannot be fulfilled, for example in the case of religious conversion that occurs after a marriage in Islam. According to the Compilation of Islamic Law, the change of religion for both husband and wife resulted in the marriage being invalid (haram).The problem under study is